Seasonal dynamics of manganese and iron compounds in the superficial waters of Vidsichne water intake of Teteriv River - Аrystarkhova, Еlla (ScienceRise: Biological Science, 2018)
Research aim – to determine features of the season dynamics of concentrations of manganese (Мn) and iron (Fe) in the surface waters of Vidsichne water intake, Teteriv river in 2012–2014 and clarification of their correlations with the water temperature, hydrogen index (рН), content of dissolved oxygen (DO), and also by the number of dominating associations of planktonic algae. Methods. Water samples (1 dm3) were taken from the water intake (at realizing arrangements for cleaning and deepening its bottom part), and Mn and Fe compounds concentrations were determined in them by colorimetric methods, DO – by DO 4000 measurer, hydrogen index – by рН-meter, temperature – by the mercury thermometer. For studying the phytoplankton content, there was realized the hydrobiological analysis. The statistical processing of data was realized by MO Excel 2003 program. Research results. Mn compounds concentration in water exceeded MPCw and had two peak values in summer. Fe compounds were also observed in increased amounts, but their peak was in another season every year. There were revealed reliable correlations of strong and middle Mn concentrations in water with a temperature and DO. The tendency to strengthening correlations of concentrations of these compounds with blue-green algae and weakening – with green ones was demonstrated. Mutual connections of Fe with these parameters were in whole weaker comparing with Mn, especially with рН and planktonic algae. And only in 2014 coefficient values of correlation between iron and temperature and DO essentially grew. Conclusions. It was established, that concentrations of Mn and Fe compounds in water of the water intake exceeded MPCw during most seasons (0,1 and 0,3 mg/dm3 respectively) in 2-8 times. The most content of Mn was observed especially in summer months, and Fe – in different seasons. Changes of Mn concentrations were much stronger connected with the water temperature (0,7029, р≤0,01 – in 2012 and 0,6702, р≤0,05 – 2013 years) and DO (-0,6272, р≤0,05 – in 2012, -0,8752, р≤0,0001 – 2013 and -0,6349, р≤0,05 – 2014 years), than ones of Fe concentrations. Correlations of Fe compounds with these parameters reaches reliability only in 2014 year (0,7326 and -0,7469 respectively, р≤0,01). Mn and Fe compounds had reliable connections only with blue-green algae (cyanogen bacteria) among all phytoplankton associations: Mn (0,6808, р≤0,05) – in 2014 and Fe (0,7410, р≤0,01) – in 2012. During the three year period of the studies there was fixed weakening connections between Mn and water temperature (by 28,54 %) and amounts of green algae (by 65,63 %) and strengthening – with amounts of blue-green ones (by 77,95 %), and also the growing dependence of Fe compounds concentrations on the temperature (by 79,12 %) and DO (by 95,77 %). Most revealed tendencies (except season dynamics of Mn and its correlations with the temperature, DO and amounts of blue-green ones) were atypical for the water intake and appeared, most probably, as a result of arrangements for cleaning the bottom part of the water body and its deepening that resulted in disorders in the condition of the water environment, including the abnormal increase of blue-green algae amounts in December of 2012 (up to 91,06 thousand cl/dm3)